Correction: Aleem et al. Whole-Genome Identification of APX and CAT Gene Families in Cultivated and Wild Soybeans and Their Regulatory Function in Plant Development and Stress Response. Antioxidants 2022, 11, 1626 - Muqadas Aleem; Saba Aleem; Iram Sharif; Maida Aleem; Rahil Shahzad; Muhammad Imran Khan; Amina Batool; Gulam Sarwar; Jehanzeb Farooq; Azeem Iqbal; Basit Latief Jan; Prashant Kaushik; et al. (Antioxidants)
In the original publication [...]